The accuracy and precision of plain CT chest for diagnosis of anaemia - Mahnoor Hafeez; Amjad Sattar; Nasreen Naz (Journal of the Pakistan Medical Association)
Objective: To determine the accuracy and precision of anaemia diagnosis with plain computed tomography of chest by keeping complete blood count as the gold standard.